REVOLUSI MENTAL DALAM PERSPEKTIF AL-QUR’AN: STUDI PENAFSIRAN M. QURAISH SHIHAB - Saifuddin, Saifuddin (MAGHZA, 2016)
This paper is study about mental revolution which is being meant as basic change of mindset from the people and government in the context of nation and state. It is very interesting to be studied from multi perspectives. So far, this idea of mental revolution has been studied by several perspective: politic, economy, social, culture, education and in perspective of religion so rarely. This paper tried to giving Islamic perspective specially quranic perspective. QuraishShihab perspective as scholar of Quran studies will be more concern od mental revolution .This Indonesia Islamic scholar have serious concern of social change theme in the society in the qur’an include changing of mental and mindset.